2005
DOI: 10.1021/ct049841c
|View full text |Cite
|
Sign up to set email alerts
|

From Hydrophobic to Hydrophilic Solvation:  An Application to Hydration of Benzene

Abstract: We report a computer simulation study on the hydration of benzene, which, despite being hydrophobic, is a weak hydrogen bond acceptor. The effect of benzene-water hydrogen bonding on the hydration free energy has been analyzed in terms of solute-solvent energies and entropies. Our calculations show that benzene-water hydrogen bonding restricts the number of arrangements possible for the water molecules resulting in a more unfavorable (negative) solute-solvent entropy change than observed for a 'nonpolar benzen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(80 citation statements)
references
References 37 publications
3
77
0
Order By: Relevance
“…This is readily understandable if the clustering of water around large hydrophobic residues is considered. For instance, the large value of ln γ for the napsylate salt may be due in some part to the more unfavorable entropic contribution exhibited by aromatic compounds (33,34).…”
Section: Aqueous Solubilitymentioning
confidence: 99%
“…This is readily understandable if the clustering of water around large hydrophobic residues is considered. For instance, the large value of ln γ for the napsylate salt may be due in some part to the more unfavorable entropic contribution exhibited by aromatic compounds (33,34).…”
Section: Aqueous Solubilitymentioning
confidence: 99%
“…[25] The all-atom benzene model includes a permanent charge distribution, which can be expressed by an electrostatic multipole expansion where the quadrupole moment is the first nonzero term. The thermodynamic properties of this system (i.e., the benzene hydration enthalpy and entropy at infinite dilution) were calculated and showed differences of % 5 % (entropy) and % 1 % (enthalpy) compared to the experimentally reported values at 298 K. [26] Molecular dynamics simulations were performed using the Gromacs 3.2.1 MD simulation package. [27,28] All simulations were performed at constant volume and temperature (T = 298 K) using a Berendsen weak-coupling thermostat, [29] with relaxation time t = 0.1 ps.…”
Section: Molecular Dynamics Implementationmentioning
confidence: 99%
“…This exact enthalpyentropy compensating contribution has been described in several earlier works, 1,4-13 but its quantitative evaluation in numerical simulations remains challenging, and only a few numerical studies have been reported on this subject so far. 1,4,7,[9][10][11] This paper is organized as follows. In section 2, we start with describing the statistical mechanics basis of the solvation entropy.…”
Section: Introductionmentioning
confidence: 99%